Strauss's handbook of business information : a guide for librarians, students, and researchers - Moss, Rita W.; Ernsthausen, David G.; Strauss, Diane Wheeler (Santa Barbara, Calif. : Libraries Unlimited, 2012)
This new edition of Strauss's classic handbook will retain its place as an essential text for library students; an indispensable guide for practitioners in public, academic, and special libraries who deal with business inquiries; and a resource for entrepreneurs and business professionals.
Basic resources, print & Internet -- Selected, consolidated electronic business information -- Company information -- Industry information -- Government information and services -- Statistics -- Marketing -- Accounting and taxation -- Money, credit, and banking -- Investments : an introduction -- Stocks -- Bonds and other fixed-income securities -- Mutual funds and investment companies -- Futures and options -- Insurance -- Real estate -- Appendix A: Business acronyms and abbreviations -- Appendix B: Federal government departments and selected agencies relevant to business -- Appendix C: Federal government corporations and independent agencies relevant to business -- Appendix D: Representative types of business information published by state government agencies -- Appendix E: Key economic indicators -- Appendix F: Selected web sites for free business information -- Appendix G: Finding business case studies.
Includes bibliographical references and indexes.
Keywords: Business -- Reference books -- Bibliography -- Handbooks, manuals, etc; Business information services -- United States -- Handbooks, manuals, etc; Government publications -- United States -- Handbooks, manuals, etc; Business -- Databases -- Handbooks, manuals, etc; Business -- Electronic information resources -- Handbooks, manuals, etc